Abstract 039: Angiographic Outcomes of Woven EndoBridge and Balloon‐Assisted Coiling for the Treatment of Ruptured Wide‐Necked Aneurysms - Aaron Rodriguez Calienes; Juan Vivanco‐Suarez; Milagros Galecio‐Castillo; Bradley Gross; Mudassir Farooqui; Oktay Algin; Chaim Feigen; David Altschul; Santiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology)
Introduction The optimal endovascular approach for wide‐neck intracranial aneurysms (IAs) during the acute phase of bleeding remains uncertain, and the use of stent‐assisted coiling or flow diversion is controversial due to antiplatelet therapy requirements and potential risks (1, 2). Various techniques have been developed to address these challenges, including balloon‐assisted coiling (BAC) and intrasaccular flow‐disruption. The Woven EndoBridge (WEB) is a flow disrupter that has gained popularity in treating ruptured IAs due to its effectiveness in occluding aneurysms with minimal rebleeding (3, 4). The aim of this study is to provide outcome comparisons between WEB and BAC in a specific cohort of patients with ruptured wide‐necked IAs. Methods In this international cohort study, we included consecutive patients treated for ruptured wide‐neck IAs with either WEB or BAC at three neurovascular centers. The primary effectiveness outcome was complete aneurysm occlusion at the final imaging follow‐up using the Raymond‐Roy (RR) occlusion classification. Secondary outcomes included favorable functional outcome and periprocedural hemorrhagic/ischemia‐related complications. Comparisons were performed using multivariable logistic and ordinal regressions. Results One hundred four patients treated with WEB and 107 patients treated with BAC were included. The mean length of imaging follow‐up was 17.5 (± 17.6) months in the WEB group and 11.8 (± 10.3) months in the BAC group (p = 0.142). Of the patients, 60.5% in the WEB group and 53% in the BAC group achieved complete occlusion, with no significant difference between the two groups after adjusting for covariates (adjusted OR [aOR] = 1.02; 95% CI 0.46 – 2.25; p = 0.964). The odds of favorable functional outcome did not significantly differ between the WEB (74.8%) and BAC groups (77.4%, aOR = 1.45; 95% CI 0.65 – 3.24; p = 0.368). Procedure‐related complications were similar in both groups (WEB: 9.6%, BAC: 10.3%, p = 0.872). There was no statistically significant difference observed in the rates of ischemic events (WEB: 6.7% vs. BAC: 2.8%, p = 0.180) and hemorrhagic events (WEB: 3.8% vs. BAC: 7.5%, p = 0.255) between the two groups. Conclusion In conclusion, both WEB and BAC techniques showed similar effectiveness and safety outcomes in treating ruptured wide‐neck IAs. Further research and direct comparative studies are needed to better guide treatment decisions for this patient population.